Family Matters: Nippon Kaigi and Keeping Things Normal. Issue 3 (2nd September 2019) - Toyoda, Etsuko; Chapman, David
ABSTRACT: This study focuses on the discourse around social morals relating to the family that appear in written material and videos produced by conservative intellectuals belonging to the Nippon Kaigi (The Japanese Nationalist Association), which further their agenda of surveillance and control over the Japanese population. In particular, we focus on discourse on the contentious issue of fūfubessei (the retention of former family names after marriage). Here we aim to understand (1) the reasoning of their core argument that adopting fūfubessei will lead to the collapse of family, society and the Japanese nation, (2) the ideology behind this argument, and (3) the rhetoric used in attempts to persuade the public. We posit that the hostility towards fūfubessei is a reflection of the broader agenda of conservatism which leverages a moral imperative to protect traditional and normative notions of family and, ultimately, what it means to be Japanese.